Contrastive Corpus Studies in Language Teaching: A Bibliometric and Systematic Review of Language Pairs - Yulian, Yulia; Mulyati, Yeti; Widia, Ida (Journal of Languages and Language Teaching, 2025)
Corpus-based contrastive studies have become increasingly vital in language education, offering empirical insights into cross-linguistic structures, discourse patterns, and semantic strategies. However, a comprehensive synthesis mapping recent developments and identifying existing research gaps has been lacking. This study addresses this need by conducting a systematic literature review and bibliometric analysis of 73 peer-reviewed articles published between 2014 and 2024. Using PRISMA 2020 guidelines and tools such as VOSviewer, the study maps dominant linguistic focuses, frequently analyzed language pairs, and collaboration networks. The findings reveal a strong emphasis on discourse and semantics, with English commonly paired with Spanish, Arabic, and Chinese. Pragmatic dimensions and underrepresented language pairs, particularly from Southeast Asia and Africa, remain largely overlooked. The study also highlights geographic disparities in global contributions, suggesting the need for more inclusive and collaborative research frameworks. The results offer practical implications for pedagogy, policy, and research. For pedagogy, integrating corpus-informed, contrastive materials into language instruction can enhance learners’ awareness of discourse conventions and intercultural variation. In terms of policy, stakeholders are encouraged to invest in open-access multilingual corpora and support cross-border collaboration, particularly involving underrepresented linguistic communities. For future research, this study underscores the need to explore pragmatic features, diversify language pairings, and build interdisciplinary networks to promote a more equitable and context-sensitive development of corpus-based contrastive inquiry in language education.